Exploring Unique Insights into Cell Damage Pathways in Celiac Disease - Anna Maria Prenga; Besfort Korumi; Esja Shurdhi; Kenado Prela; Nandito Belba; Teona Bushati (Albanian Journal of Trauma and Emergency Surgery, 2025)
Introduction: Celiac disease, or celiac sprue, is a T cell-mediated autoimmune disorder of the small intestine triggered by ingesting dietary gluten products in genetically susceptible individuals. The pathologic mechanism involves an immune response targeting gluten peptides, leading to inflammation, villous atrophy, and malabsorption in the small intestine. This research is a significant step in understanding the mechanisms of how CD4+ T cell (white blood cells that are an essential part of the human immune system) responses against gluten can lead to autoreactive B-cell responses and tissue destruction mediated by intraepithelial cytotoxic T cells in the small intestine. Your work in this field is crucial in advancing our understanding and managing celiac disease.